CHANGES IN DIALECTS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Dialectal variation is an integral aspect of linguistic evolution, influenced by social, geographic, and historical factors. This article examines the dynamics of dialect changes, exploring causes such as migration, technology, and globalization. We analyze specific case studies to illustrate the fluidity of dialects and their impact on identity and communication. Understanding these changes is essential for linguists, sociologists, and educators in a rapidly evolving world.